Once There Were Castles : Lost Mansions and Estates of the Twin Cities - Millett, Larry (Book collections on Project MUSE., 2011)
In Lost Twin Cities, Larry Millett brought to life the vanished architecture of downtown Minneapolis and St. Paul. Now, in Once There Were Castles, he offers a richly illustrated look at another world of ghosts in our midst: the lost mansions and estates of the Twin Cities. Nobody can say for sure how many lost mansions haunt the Twin Cities, but at least five hundred can be accounted for in public records and archives. In Minneapolis and St. Paul, entire neighborhoods of luxurious homes have disappeared, virtually without a trace. Many grand estates that once spread out over hundreds of acres.